Effect of the Camelid’s Seminal Plasma Ovulation-Inducing Factor/β-NGF: A Kisspeptin Target Hypothesis - El Allali, Khalid; El Bousmaki, Najlae; Ainani, Hassan; Simonneaux, Valérie (Frontiers in Veterinary Science, 2017)
Female mammals are classified into spontaneous and induced ovulators based on the mechanism eliciting ovulation. Ovulation in spontaneous species (e.g., human, sheep, cattle, horse, pigs, and most rodents) occurs at regular intervals and depends upon the circulating estradiol. However, in induced ovulators (e.g., rabbits, ferrets, cats, and camelids) ovulation is associated with coitus. In the later, various factors have been proposed to trigger ovulation, including auditory, visual, olfactory and mechanic stimuli. However, other studies have identified a biochemical component in the semen of induced ovulators responsible for the induction of ovulation and named accordingly ovulation inducing factor. In camelids, intramuscular or intrauterine administration of seminal plasma was shown to induce the preovulatory LH surge followed by ovulation and subsequent formation of corpus luteum. Recently, this ovulation inducing factor has been identified from seminal plasma as a neurotrophin, the nerve growth factor ß (ß-NGF). ß-NGF is well known as promoting neuron survival and growth, but in this case, it appears to induce ovulation through an endocrine mode of action. Indeed, ß-NGF may be absorbed through the endometrium to be conveyed, via the blood stream, to the central structures regulating the LH preovulatory surge. In this review we provide a summary of the most relevant results obtained in the field and we propose a working hypothesis for the central action of ß-NGF based on our recent demonstration of the presence of neurons expressing kisspeptin, a potent stimulator of GnRH/LH, in the camel hypothalamus.